How Nurse Work Environments Relate to the Presence of Parents in Neonatal Intensive Care - Hallowell, Sunny G. (Adv Neonatal Care, 2019)
BACKGROUND: Parental presence in the neonatal intensive care unit (NICU) is essential for families to participate in infant care and prepare them to transition from hospital to home. Nurses are the principal caregivers in the NICU. The nurse work environment may influence whether parents spend time with their hospitalized infants. PURPOSE: To examine the relationship between the NICU work environment and parental presence in the NICU using a national data set. METHODS: We conducted a cross-sectional, observational study of a national sample of 104 NICUs, where 6060 nurses reported on 15,233 infants cared for. Secondary analysis was used to examine associations between the Practice Environment Scale of the Nursing Work Index (PES-NWI) (subscale items and with a composite measure) and the proportion of parents who were present during the nurses’ shift. RESULTS: Parents of 60% (SD = 9.7%) of infants were present during the nurses’ shift. The PES-NWI composite score and 2 domains—Nurse Participation in Hospital Affairs and Manager Leadership and Support—were significant predictors of parental presence. A 1 SD higher score in the composite or either subscale was associated with 2.5% more parents being present. IMPLICATIONS FOR PRACTICE: Parental presence in the NICU is significantly associated with better nurse work environments. NICU practices may be enhanced through enhanced leadership and professional opportunities for nurse managers and staff. IMPLICATIONS FOR RESEARCH: Future work may benefit from qualitative work with parents to illuminate their experiences with nursing leaders and nurse-led interventions in the NICU and design and testing of interventions to improve the NICU work environment.